"Främlingen" bland svensk "Homo Academicus" (Sociologisk Forskning, 2017)
The ”stranger” among Swedish ”Homo Academicvs”This paper is about individuals with immigrant background among the Swedish academic elite, i.e. those who have a PhD and work at Swedish universities. The aim of the study is to understand how factors other than academic qualifications, such as gender and a migrant background, may impact on the individual’s ability to get a job and pursue a successful career in Swedish higher education. The data used for this study is obtained from the Longitudinal Database of Education, Income and Occupation (LISA) administered by Statistics Sweden.When compared to the reference group (individuals born in Sweden with at least one Swedish-born parent), the results show that given the same work experience individuals born in Eastern Europe, Asia, Africa and South America are more likely to be unemployed. Among those who have a job, those